0140 In situ simulation helps in identification of latent errors and improves knowledge: Multi centre, multispecialty study project. (2nd November 2015) - Farooq, Omer; Quayle, Alexandra; Fent, Graham; Blythe, James; Purva, Makani
Abstract : Introduction: In situ simulation helps in identification of latent errors (potential hazards in workplace) 1 and improves knowledge. At present no reliable method could help identify and grade the latent errors across different specialties. By conducting cross specialty, multi site study we aim to establish efficiency of in situ simulation in identifying latent errors, grading risk using NPSA risk matrix 2 across different specialties and improve knowledge. Methods: So far 47 participants have participated in this prospective study. Participants had paediatrics, anaesthesia, obstetrics, A&E, midwifery and nursing background. Acute scenarios targeting individual specialty needs were delivered with multidisciplinary team participating in the exercise. Latent errors highlighted were graded according to NPSA risk matrix and respective departments were informed with recommendations to resolve the issues. Immediate pre and post simulation questionnaire were completed and a follow up 6 weeks questionnaire will be sent to the participants. Qualitative and quantitative methods are employed. Results: Our results demonstrate that 19 latent errors (Equipment 2, Environment 2, Medicine 2, Training 13) have been highlighted, graded according to NPSA risk matrix and subsequent recommendations have been made to parent departments. 65% participants felt considerably confident in management of unwell patient, 87% were able to positively able to identify changes required to improve individual and team performance. 80% had knowledge gaps sufficiently highlighted by in situ simulation exercise. More than 60% of the participants rated feedback as very constructive. About 80% highly recommended regular in situ simulation sessions. Impact on practice: Use of in situ simulation across different specialties has helped us identify latent errors and improve participants' knowledge. We are able to apply NPSA risk matrix across various specialties with relative ease and found it useful in risk gradation. As it is an on going project, we hope to have further data to strengthen our findings. References: Patterson MD, Geis GL, Falcone RA, et al . In situ simulation: detection of safety threats and teamwork training in a high risk emergency department. BMJ Qual Saf. 2013;22(6):468–77 National Patient Safety Agency. A risk matrix for risk managers. NHS 2008